Experiences of Adults High in the Personality Trait Sensory Processing Sensitivity: A Qualitative Study - Sharell Bas (MDPI AG, 2021)
Sensory processing sensitivity (SPS) is a personality trait reflecting inter-individual differences in sensitivity to negative and positive environmental information. Being high in SPS is associated with increased stress-related problems if environments are unfavourable but also appears to enhance one’s ability to benefit from health-promoting environments. In understanding SPS, therefore, lies the potential for innovating the ways we use to promote mental health. However, as a young research field, the core characteristics of SPS are yet debated. Qualitative research interviewing highly sensitive adults is important to conduct ecologically valid research connected with the complex realities of people. This study was the first to systematically report the perceptions and experiences of SPS characteristics in adults high in this trait. Semi-structured interviews (n = 26) were analysed thematically and described following consolidated criteria for reporting qualitative research. Six themes emerged: (1) emotional responding; (2) relatedness to others; (3) thinking; (4) overstimulation; (5) perceiving details; and (6) global SPS characteristics. With regards to coping with negative consequences of high SPS, the main themes were: (1) reducing sensory input and (2) psychological strategies. We gained fine-grained information on experiences of adults high in SPS and derived new hypotheses regarding the fostering of well-being related to high SPS.